2015
DOI: 10.1007/s10753-015-0174-5
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Sodium Aescinate on Cutaneous Wound Healing in Diabetic Rats

Abstract: This study is aimed to evaluate the potential effects of sodium aescinate (SA, the sodium salt of aescin) on wound healing in streptozotocin-induced diabetic rats. An excision skin wound was created in diabetic rats, and the wounded rats were divided into three groups: I) control group, II) gel-treated group, and III) SA-treated group. The control group wounds received topically normal saline once daily for 19 days. The gel-treated and SA-treated wounds received topically 400 μl of pluronic F-127 gel (25%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This shows that hyperglycemic metabolic impairment affects wound healing ability. Chronic wound healing in diabetic patients usually manifests badly in diabetic ulcer, and this occurs as a consequence of excess reactive oxygen species (ROS) and dysfunctional inflammatory function [21,25]. It is usually characterized by continual influx of neutrophils that release cytotoxic enzymes and inflammatory mediators that cause damage to surrounding tissue [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that hyperglycemic metabolic impairment affects wound healing ability. Chronic wound healing in diabetic patients usually manifests badly in diabetic ulcer, and this occurs as a consequence of excess reactive oxygen species (ROS) and dysfunctional inflammatory function [21,25]. It is usually characterized by continual influx of neutrophils that release cytotoxic enzymes and inflammatory mediators that cause damage to surrounding tissue [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lipid peroxidation is suspected to impair VEGF expression for normal angiogenesis process [35]. Antioxidant agents are effective to combat excessive ROS activity and thus minimize lipid peroxidation [22,25]. TQ has shown to improve endothelial function by reducing oxidative stress [36].…”
Section: Discussionmentioning
confidence: 99%
“…Many research studies have demonstrated that SA exerts anti-inflammatory and antioxidant effects, suggesting a mechanism for its myocardial protective effects [12]. AOPP induced many complications, including myocardial injury, partly due to oxidative damage and apoptosis of myocardial cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…β-sodium aescinate is a sodium containing compound extracted from the Saul son fruit (traditional Chinese medicine), with anti-inflammatory properties (5). …”
Section: Discussionmentioning
confidence: 99%
“…β-sodium aescinate is a sodium containing compound extracted from the Saul son fruit (traditional Chinese medicine), with anti-inflammatory properties (5). It is known (6) that β-sodium aescinate has relatively good efficacy in treating ischemia-reperfusion injury after acute cerebral hemorrhage and brain edema.…”
Section: Introductionmentioning
confidence: 99%